Kajian Filosofi Tradisi Ngejot Banten Pada Hari Suci Galungan Di Desa Wanagiri Kabupaten Buleleng - Luh Putu Cita Ardiyani; Ida Bagus Wika Krishna; Ida Bagus Putu Eka Suadnyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The tradition of ngejot banten on the holy day of Galungan in Wanagiri Village is a tradition that is continuously implemented and passed down from generation to generation which is believed to have deep meaning for the people of Wanagiri Village. Based on this background, the problems that can be formulated are: 1) Why is the tradition of ngejot banten on the holy day of Galungan in Wanagiri Village implemented? 2) What is the form of the implementation of the tradition of ngejot banten on the holy day of Galungan in Wanagiri Village? 3) What is the philosophical meaning of the tradition of ngejot banten on the holy day of Galungan in Wanagiri Village?. The theory used to examine the problem is the direction and footing for the author, namely: 1) Symbolic interactionism theory which will be used to dissect the problem regarding the basis for implementing the tradition of ngejot banten on the holy day of Galungan in Wanagiri Village. 2) The religious theory that will be used to dissect the problems regarding the form of implementation and the philosophical meaning of the ngejot banten tradition on the Galungan holy day in Wanagiri Village. The data analysis process will produce 1) The basis for carrying out the tradition of ngejot banten on the holy day of Galungan in Wanagiri Village includes: the history of the tradition of ngejot banten on the holy day of Galungan, Means of establishing kinship relations (Families of dadia), Means of introduction, Means of devotion to ancestors. 2) The form of the implementation of the tradition of ngejot banten on the holy day of Galungan in Wanagiri Village includes: the preparation stage (the giver and recipient), the stage of the natab ceremony procession in the bale, the ceremonial facilities used. 3) The philosophical meanings contained in the tradition of ngejot banten on the holy day of Galungan in Wanagiri Village include: 1) The meaning of ethics, 2) The meaning of tattwa, 3) The meaning of aesthetics